2022
DOI: 10.48550/arxiv.2202.10115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Smoothing and Thresholding Image Segmentation Framework with Weighted Anisotropic-Isotropic Total Variation

Abstract: In this paper, we propose a multi-stage image segmentation framework that incorporates a weighted difference of anisotropic and isotropic total variation (AITV). The segmentation framework generally consists of two stages: smoothing and thresholding, thus referred to as SaT. In the first stage, a smoothed image is obtained by an AITV-regularized Mumford-Shah (MS) model, which can be solved efficiently by the alternating direction method of multipliers (ADMM) with a closed-form solution of a proximal operator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Subsequently, the AwTV algorithm has been widely used and developed in image reconstruction, denoising, and restoration. 11,12 These TV variants algorithms [13][14][15] and the improvement of the optimization method significantly promote the development of sparse-view reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the AwTV algorithm has been widely used and developed in image reconstruction, denoising, and restoration. 11,12 These TV variants algorithms [13][14][15] and the improvement of the optimization method significantly promote the development of sparse-view reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25,28,39,42,44], 1 / 2 [53,63,66], and an error function [30]. Lou et al [45] designed a TV version of 1 − α 2 called the weighted anisotropic-isotropic total variation (AITV), which outperforms TV in various imaging applications, such as image denoising [45], image reconstruction [45,39], and image segmentation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose an AITV variant of (4) to improve the smoothing step of the SaT/SLaT framework for images degraded by Poisson noise and/or blur. Incorporating AITV regularization is motivated by our previous works [8,9,50], where we demonstrated that AITV regularization is effective in preserving edges and details especially under Gaussian and impulsive noise. To maintain similar computational efficiency as the original SaT/SLaT framework, we propose an ADMM algorithm that utilizes the 1 − α 2 proximal operator [43].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of nonconvex regularization include ℓ p , 0 < p < 1 (Chartrand, 2007;Cao et al, 2013), et al, 2015a,b;Ding and Han, 2019;Li P. et al, 2020;Ge and Li, 2021), ℓ 1 /ℓ 2 (Rahimi et al, 2019;Wang et al, 2020;Xu et al, 2021), and an error function (Guo et al, 2021). Lou et al (2015c) designed a TV version of ℓ 1 − αℓ 2 called the weighted difference of anisotropic-isotropic total variation (AITV), which outperforms TV in various imaging applications, such as image denoising (Lou et al, 2015c), image reconstruction (Lou et al, 2015c;Li P. et al, 2020), and image segmentation (Bui et al, 2021(Bui et al, , 2022Wu et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose an AITV variant of (4) to improve the smoothing step of the SaT/SLaT framework for images degraded by Poisson noise and/or blur. Incorporating AITV regularization is motivated by our previous works (Park et al, 2016;Bui et al, 2021Bui et al, , 2022, where we demonstrated that AITV regularization is effective in preserving edges and details, especially under Gaussian and impulsive noise. To maintain similar computational efficiency as the original SaT/SLaT framework, we propose an ADMM algorithm that utilizes the ℓ 1 − αℓ 2 proximal operator (Lou and Yan, 2018).…”
Section: Introductionmentioning
confidence: 99%